HUBUNGAN ANTARA PENGETAHUAN MASYARAKAT DENGAN KEPATUHAN PENGGUNAAN MASKER SEBAGAI UPAYA PENCEGAHAN PENYAKIT COVID-19 DI NGRONGGAH - Devi Pramita Sari; Nabila Sholihah ‘Atiqoh (Universitas Duta Bangsa Surakarta, 2020)
Covid-19 is a disease caused by a corona virus that makes a pandemic in all countries, especially Indonesia. Covid 19 disease can be prevented including knowledge and compliance of the public in the use of masks as an effort to prevent Covid-19 disease. Preliminary preliminary survey revealed that there were 3 respondents with bad knowledge and 6 people in RT03 / RW08 Ngronggah were not compliant to wear masks. The purpose of this study was to determine the relationship between community knowledge and compliance with the use of masks as an effort to prevent Covid-19 in Ngronggah. This research was conducted using a descriptive quantitative survey method with cross sectional study approach. The population and sample were taken in total sampling, that is, all 62 RT RT / RW 08 Ngronggah communities. The research instrument used questionnaires and observation guidelines. Quantitative data analysis uses the chi-square relationship test. The results of this study of 62 respondents based on the results of the Chi-Square test of significance of p between independent variables namely community knowledge with the dependent variable compliance with the use of masks by 0.004 (p <0.05) then Ho was rejected and stated there was a relationship. The conclusion is that there is a relationship between public knowledge and compliance with the use of masks as an effort to prevent Covid-19 disease in Ngronggah. Suggestions should provide education about the importance of using masks to prevent and avoid the risk of Covid-19 disease